FRAUDULENT FINANCIAL REPORTING: ANALISIS PENGARUH ELEMEN FRAUD HEXAGON PADA PERUSAHAAN FARMASI - Gunawan, Gilbert Outner; Siregar, Anitaria (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
This study analyses the influence of fraud hexagon dimension towards fraudulent financial statement. Fraudulent financial statement is measured using Beneish M-Score Model. Six dimension of the fraud hexagon is being considered influence fraudulent financial statement. The population on this study are pharmacy companies which being registered in Indonesia Stock Exchange for period 2020-2021. This study uses purposive sampling with final sample 48 companies. The result shows stimulus/pressure (financial stability) has the influence towards fraudulent financial statement, while opportunity (ineffective monitoring), rationalization (change in auditor), capability (change in director), ego/arrogance (frequent number of CEO’s picture), and collusion (cooperation with government project) do not have influence towards fraudulent financial statement.